REKONTEKSTUALISASI SEMIOTIKA FERDINAND DE SASSURE DALAM MEMAKNAI KONSEP CAHAYA SEBAGAI HIDAYAH: ANALISISQ.S AN-NUR: 35 - Djamali Mokoginta (CV. Adiba Aisha Amira, 2024)
This article examines the recontextualization of Ferdinand de Saussure's semiotics in understanding the concept of light as guidance, focusing on the analysis of QS. An-Nur: 35. The symbol of